Space-saving tips to lower stress. Issue 3 (March 2018) - Gordon, Vernita
Understanding how some single cells evolved into multicellular life means figuring out how they overcome the stresses associated with crowding as they multiply. New insights from yeast suggest that changes in the shape of cells may provide an answer.